IMPLEMENTASI KEBIJAKAN TIGA SURAT IZIN PRAKTIK DOKTER SPESIALIS TERHADAP KUALITAS PELAYANAN RAWAT JALAN DI RSUD ARIFIN NU'MANG KABUPATEN SIDENRENG RAPPANG - Henny Irawati; Muhammad Nur; Andi Nilwana; Muhammad Rais Rahmat Razak; Aman Darmawan (LPPM Universitas Abdurrab, 2026)
This study analyzes the implementation of the three Practice Licenses (SIP) policy for specialist doctors and its impact on outpatient service quality at Arifin Nu'mang Regional Hospital, Sidenreng Rappang Regency. The policy regulated under Law Number 17 of 2023 on Health and the Ministry of Health Circular Letter Number HK.02.01-MENKES-6-2024 allows specialist doctors to practice at three different health facilities. This study employed a quantitative method with a descriptive approach involving 396 outpatient respondents. Data were analyzed using simple linear regression, multiple linear regression, and mediation tests. The results showed that the implementation of the three SIP policy significantly influenced patient waiting time (B=0.610; p<0.001; R²=0.400) and service quality (B=0.722; p<0.001; R²=0.474). However, waiting time did not significantly affect service quality (B=0.089; p=0.083) and did not mediate the relationship between policy implementation and service quality (Z=1.730; p=0.084). These findings confirm that policy implementation directly influences service quality without going through the waiting time variable, indicating that service quality perception is more determined by the interpersonal aspects of doctors rather than the technical factor of waiting time.